Interaction between felsic and mafic magmas in the Salmas intrusive complex, Northwestern Iran: constraints from petrography and geochemistry - Ghaffari, M.
The Salmas plutonic complex, in the northernmost part of Sanandaj-Sirjan Zone of Iran, provides evidence for magma interaction processes. The complex contains mafic-intermediate, hybrid and felsic rocks which intruded into the Paleozoic metamorphic complex. They show typical relationships described in many mafic–felsic mingling and mixing zones worldwide, such as mafic microgranular enclaves (in felsic and hybrid rocks), mafic sheets, and hybrid rocks. The mafic microgranular enclaves (MMEs) are characterized by fine-grained, equigranular and hypidiomorphic texture and some special types of microscopic textures, e.g., quartz xenocrysts, oscillatory-zoned plagioclase, small lath-shaped plagioclase in large plagioclase, spike zones in plagioclase and spongy-cellular plagioclase textures, rounded plagioclase megacrysts blade-shaped biotite, acicular apatite. The mafic sheets and MMEs in granites (MME-Gr), which indicated magma mingling structures, show ISr values and eNd(i) similar to diorites. The hybrid rocks and their mafic enclaves (MME-H) show isotope signatures similar to each other. Granites have isotope signatures [higher 87Sr/86Sr(i) (0.70788–0.71075) and lower eNd(i) ( 2.4 to 4.2)] distinct to those of the all rock types and MMEs. Major, trace and REE modeling show that hybrid rocks are generated via 40–60% mixing of mafic (dioritic) and felsic (granitic) end-members. All the geochemical data suggest that underplating of dioritic magma, which has been produced by fractional crystallization of gabbros, under the lower crust caused its melting to make felsic (granitic) magma. Injection of dioritic magma into the base of the felsic magma chamber and a limited mixing of two end-members, the lower crust-derived magma and mantle-derived melts, formed hybrid magma and their enclaves. Injections of new mafic magma pulses into hybrid magma generated mafic enclaves into them. The injections of denser dioritic magma pulses into a felsic magma chamber and spreading of it at the level of rheological contrast have been formed mafic sheets and MMEs in granites.